The Effectiveness of Deep Learning based PjBL on Student’s Scientific and Critical Thinking Skills at Indonesia - Taufik; Mohammad Edy Nurtamam; Dewanto; Tomi Apra Santosa (Postgraduate, University of Mataram, 2025)
Many studies have examined the effect of project-based learning on students' scientific and critical thinking skills, but no research has examined the effect size of the Deep Learning-based PjBL model on students' scientific and critical thinking skills in Indonesia. The integration of deep learning principles into Project-Based Learning (PjBL) gave birth to the Deep Learning-based PjBL model that encourages students to construct knowledge through real projects, continuous reflection, and collaboration. This study aims to determine the learning model of project-based learning based on deep learning on students' scientific and critical thinking skills. This type of research is quantitative research with a meta-analysis method. The inclusion criteria in this study are research data derived from journals indexed by Sinta or Scopus, articles published in 2021-2025, research must be experimental or quasi-experimental methods, relevant research, data obtained through the Google Scholar, ERIC, ScienceDirect, and Taylor of Francis databases, and published journals have complete data to calculate the effect size value. Data analysis using the JASP application. This study analyzed 17 relevant articles. The results concluded that the summary effect size value was d = 0.88; t = 8.26; p < 0.005, a high effect size category. These findings explain the significant influence of the deep learning-based PjBL model on students' scientific and critical thinking skills in learning. aspects to tackle this issue, particularly in low- and middle-income countries.